Preventive effect of an orthodontic compomer against enamel demineralization around bonded brackets - Alan Rafael Martins Savariz; Mariana Marquezan; Maurício Mezomo (Universidade Estadual de Campinas, 2015)
Orthodontic appliances predispose to the accumulation of plaque due to the great number of retentive sites, which might lead to enamel demineralization adjacent to the accessories. Aim: To assess the effectiveness of a compomer for orthodontic bonding in preventing the formation of white spots around orthodontic brackets. Methods: Forty extracted human premolars were divided into two groups: control group (CG), in which conventional resin Transbond™ XT Light Cure (3M Unitek™) was used to bond the brackets; and experimental group (EG), in which the compomer Transbond™ Plus Color Change (3M Unitek™) was used. pH cycling was performed for 17 days to induce the demineralization process. Enamel on the buccal face was photographed under a stereomicroscope (at 10x magnification) before (t0) and after (t1) pH cycling. The images were used to compare demineralization between the groups by using a visual scale. Results: A statistically significant difference between control and experimental groups was found (p=0.004) showing that the compomer was more efficient than the conventional resin in preventing white spots. Conclusions: The compomer Transbond Plus Color Change was capable of inhibiting enamel demineralization adjacent to the bonding area of brackets. However, the inhibition halo did not exceed 1 mm.